Therapeutic effects of life style reframing and unconscious reframing on a sexually promiscuous homosexual - Kuttikattukunnel, Francis (Animo Repository, 1994)
This study tests the therapeutic effects of Abraham C. Mattakottil's Life Style Reframing and Grinder as well as Bandler's NLP-Unconscious Reframing on the life style of a promiscuous homosexual. The focus, however, is on the client's promiscuity rather than on his homosexuality. The client approached the researcher for help in terms of dealing with the former's promiscuous sexual habits and not with his homosexual orientation. Unavailability of more willing subjects to undergo therapy was a limitation. Thus, outcome of the two therapeutic approaches may be seen only from an N=1. Replications of this study are necessary since N=1 findings can never be used for conclusive statements. The researcher conducted an intake interview to gather baseline information about the client and his family. A sexual orientation/promiscuity scale, and adapted face-validated version of Bel and Weinberg's Sexual Orientation/Promiscuity Scale, was used as one of the pre-therapy data-gathering instruments. The Life Style Interview Guide of Eckstein, Baruth and Maher (1978) was also used as a pre-therapy and post-therapy assessment tool. The Life Style Reframing Procedures consisted of two parts. Part 1 was designed for utilizing the positive experiences and memories of the individual for eliciting, modifying and expanding inner processes and responses. Part 2 was designed for dealing with the negative experiences and memories of the counselee. Three months after the therapy sessions were completed, the same Sexual Orientation/Promiscuity Scale was administered as a post-therapy test. Six months after the first post-therapy assessment, the Sexual Orientation/Promiscuity Scale and life Style Interview Guide were administered in order to assess further the long-term effect of the therapy on the client. The conclusions drawn from the study were:1. Life Style Reframing and unconscious reframing contributed to the improvement of the client's life style 2. Home environment played a role in the development of the individual's life style. An unhealthy home environment contributed to the development of an unhealthy life style and,3. Support systems established and maintained a healthy life style to answer the physical, emotional and spiritual needs of the client. It is recommended that the family must be made part of the school's sex education program. It should be included in discussions about sexual orientations. Homosexual tendencies must be identified at the earliest age possible. It is suggested that sexuality become one of the thrusts of the schools' guidance programs. Thus, proper therapeutic interventions must be introduced before emotional conflicts become more complicated.